Incorrect sleeping position and eye rubbing in patients with unilateral or highly asymmetric keratoconus: a case-control study - Mazharian, Adrien; Panthier, Christophe; Courtin, Romain; Jung, Camille; Rampat, Radhika; Saad, Alain; Gatinel, Damien (Graefe's archive for clinical and experimental ophthalmology, 2020)
Purpose To evaluate eye rubbing and sleeping position in patients with Unilateral or Highly Asymmetric Keratoconus (UHAKC). Methods Case-control study of consecutive UHAKC patients diagnosed at the Rothschild Foundation. Controls were age- and sex-matched, randomly selected refractive surgery clinic patients. Patients self-administered questionnaires regarding their family history of keratoconus, eye rubbing, and sleeping habits. All the eyes underwent a comprehensive ocular examination. Logistic regression was used to analyze univariate and multivariate data to identify risk factors for keratoconus. Results Thirty-three UHAKC patients and 64 controls were included. Univariate analyses showed that daytime eye rubbing [OR = 172.78], in the morning [OR = 24.3], or in eyes with the steepest keratometry [OR = 21.7] were significantly different between groups. Allergy [OR = 2.94], red eyes in the morning [OR = 6.36], and sleeping on stomach/sides [OR = 14.31] or on the same side as the steepest keratometry [OR = 94.72] were also significantly different. The multivariate model also showed statistical significance for most factors including daytime eye rubbing [OR = 134.96], in the morning [OR = 24.86], in the steepest eye [OR = 27.56], and sleeping on stomach/sides [OR = 65.02] or on the steepest side [OR = 144.02]. A univariate analysis in UHAKC group, comparing the worse and better eye, showed that eye rubbing [OR = 162.14] and sleeping position [OR = 99.74] were significantly ( p < 0.001) associated with the worse eye. Conclusion Our data suggests that vigorous eye rubbing and incorrect sleeping position are associated with UHAKC. This is especially true in rubbing the most afflicted eye, and contributory sleep position, including positions placing pressure on the eye with the steepest keratometry.